2021
DOI: 10.3389/froh.2021.647980
|View full text |Cite
|
Sign up to set email alerts
|

At the Crossroads of Molecular Biology and Immunology: Molecular Pathways for Immunological Targeting of Head and Neck Squamous Cell Carcinoma

Abstract: Background: Recent advances in immunotherapy for head and neck squamous cell carcinoma (HNSCC) have led to implementation of anti-programmed death receptor 1 (PD-1) immunotherapy to standard of care for recurrent/metastatic HNSCC. However, the majority of tumors do not respond to these therapies, indicating that these tumors are not immunogenic or other immunosuppressive mechanisms might be at play.Aim: Given their role in carcinogenesis as well as in immune modulation, we discuss the relation between the STAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…In HNSCCs, three pathways, STAT3, PI3K/AKT/mTOR, and Wnt, are the important signaling pathways underlying the immune evasion of HNSCCs. Therefore, targeting some molecules of these signals could contribute to facilitating immune therapies [ 130 ].…”
Section: Immunotherapymentioning
confidence: 99%
“…In HNSCCs, three pathways, STAT3, PI3K/AKT/mTOR, and Wnt, are the important signaling pathways underlying the immune evasion of HNSCCs. Therefore, targeting some molecules of these signals could contribute to facilitating immune therapies [ 130 ].…”
Section: Immunotherapymentioning
confidence: 99%
“… 62 One approach to overcome immune evasion is to target the known molecular pathways in HNSCC that are affected and associated specifically with its immune characteristics, focusing on three pathways: STAT3, PI3 K/AKT/mTOR, and Wnt pathways. 63 Recently, a study in HPV-positive HNSCC patients identified CD8+ T cell epitopes derived from the E2 immune target and detected a large number of E2-specific CD8+ T cells in the TME of such patients, demonstrating that E2 is a primary immunotherapeutic target. 64 , 65 Furthermore, the role of intracellular DNA sensor agonists in immune therapy has received increasing attention.…”
Section: Immunotherapymentioning
confidence: 99%
“…Signaling pathways are widely affected in HNSCC and are known to be involved in processes underlying immune evasion in HNSCC. Wondergem et al ( 64 ) explored three pathways: STAT3, PI3K/AKT/mTOR and Wnt, which are assumed to represent promising targets to possibly facilitate immunotherapy response. These pathways are of particular importance, because they are involved in cellular processes considered to account for primary or acquired resistance to immunotherapy.…”
Section: Biomarkers For Immunotherapy In Head and Neck Cancermentioning
confidence: 99%
“…The aim is to stop the propagation of tumor cells and stimulate the immune response at the same time by blocking responsible signaling cascades. The emphasis should be on the comparison between HPV-driven and non-driven head and neck cancer patients as different pathways seem to be relevant for their respective immune response and response to drugs ( 64 ). Oncogenic pathways that are activated through gain-of-function alterations in oncogenes or loss-of-function alterations in tumor suppressor genes are known to influence the local anti-tumor immune response.…”
Section: Biomarkers For Immunotherapy In Head and Neck Cancermentioning
confidence: 99%